2003
DOI: 10.1128/iai.71.6.3329-3336.2003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Capsular Polysaccharide from Vibrio parahaemolyticus

Abstract: The leading cause of food poisoning in both Taiwan and Japan is Vibrio parahaemolyticus infection, whose mechanism of enteropathogenesis is still unclear. To evaluate whether surface components are responsible for the intestinal adhesion of V. parahaemolyticus, we have developed a novel method for isolating the capsular polysaccharide (CPS) from V. parahaemolyticus (serotype O4:K8). We found that culturing of V. parahaemolyticus in broth for 1 week or more changed the colony form of the bacteria on an agar pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 45 publications
0
51
0
1
Order By: Relevance
“…However, the CPSA capsule is required for opacity and appears as a thick layer surrounding the cell in electron micrographs (Enos-Berlage and McCarter, 2000;Guvener and McCarter, 2003). Recent work with OP clinical isolates from Taiwan also reports that OP strains produce significantly more capsule (of K8 antigen type) than TR forms (Hsieh et al, 2003). In contrast, the O-ag capsule determines opacity in V. cholerae and the VPS determines colony rugosity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the CPSA capsule is required for opacity and appears as a thick layer surrounding the cell in electron micrographs (Enos-Berlage and McCarter, 2000;Guvener and McCarter, 2003). Recent work with OP clinical isolates from Taiwan also reports that OP strains produce significantly more capsule (of K8 antigen type) than TR forms (Hsieh et al, 2003). In contrast, the O-ag capsule determines opacity in V. cholerae and the VPS determines colony rugosity.…”
Section: Discussionmentioning
confidence: 98%
“…Vibrio parahaemolyticus strains isolated from environmental or clinical settings display reversible phase variation that is manifested by variable colony morphology (McCarter, 1999;Hsieh et al ., 2003). Phase variation is modulated by a locus encoding the transcriptional regulator OpaR (McCarter, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…in the polysaccharide capsule or glycocalyx surrounding the F. psychrophilum cells (Crump et al 2001. Capsular polysaccharides are known to be associated with phase variation (van der Woude & Bäumler 2004), adhesion ability (Hsieh et al 2003), autoagglutination and also cell surface hydrophilicity (Bonet et al 1993) in Gram-negative bacteria. A detailed characterization of the glycocalyx of the 2 colony phenotypes of F. psychrophilum is planned for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In Bifidobacterium animalis subsp. lactis, EPS production seems to be enhanced in the presence of bile (RuasMadiedo et al, 2009), as has been found for two pathogenic Vibrio species (Hsieh et al, 2003;Hung et al, 2006). Surface polysaccharides are well known as virulence and colonization factors of pathogenic bacteria, but molecules produced by commensal gut micro-organisms are gaining attention for their role in developing a normal immune system through communication with the mammalian host (reviewed by Mazmanian & Kasper, 2006).…”
Section: Introductionmentioning
confidence: 99%